Michael Jordan’s Leadership Model: The Case of The Last Dance Documentary (Third Sector Social Economic Review, 2026)
The aim of this study is to provide a theoretical contribution to the organizational behavior and leadership literature by analyzing Michael Jordan’s leadership model within the framework of The Last Dance documentary. The literature indicates that the effectiveness of authoritarian, transformational, charismatic, and situational leadership theories varies across different organizational contexts. In the research, a single case study design was employed within the qualitative research method, and the documentary The Last Dance, a production of the Entertainment and Sports Programming Network (ESPN) and Netflix, was selected as the data source. All ten episodes of the documentary were systematically reviewed, and a total of 25 leadership-related incidents were identified and analyzed using time codes. The data were examined through Braun and Clarke’s (2006) six-phase thematic analysis approach, and Jordan’s leadership behaviors were coded under four themes. The findings reveal that Jordan demonstrates a mixed leadership model by simultaneously exhibiting authoritarian, transformational, charismatic, and situational leadership characteristics. Although his pressuring approach creates psychological strain on team members, it also contributes to increased performance; moreover, he provides inspirational motivation through role-model behavior, generates charismatic influence through extraordinary performance, and adapts his leadership style according to situational conditions. The results highlight that team leadership is inherently multidimensional and context-dependent.
Keywords: Michael Jordan; Organizational Behavior; Leadership Theories; Hybrid Leadership; NBA